2013
DOI: 10.1007/s00340-013-5564-5
|View full text |Cite
|
Sign up to set email alerts
|

Yb band parasitic lasing suppression in Er/Yb-co-doped pulsed fiber amplifier based on all-solid photonic bandgap fiber

Abstract: A novel kind of all-solid photonic bandgap fiber (AS-PBGF) has been used in the master oscillator power amplifier structured Er/Yb-co-doped pulsed fiber amplifier to suppress the Yb band parasitic lasing for the power scaling and safety operation. To the best of our knowledge, this is the first time to report the use of AS-PBGF to suppress the Yb band parasitic lasing. The experimental results show that the Yb band parasitic lasing has been suppressed efficiently and the amplifier power has been raised dramati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…We name this problem optical feedback inhibition (OFI), and it may be similar to parasitic lasing (PL) also resulting from back reflection. Although parasitic lasing mostly occurs in high power or Q-switched high gain laser system, like slab laser, thin-disk laser or fiber amplifier, [13][14][15][16][17][18] and can make optical damage with spectrally bright and small spatial divergent beam, to date, no direct evidence has indicated that OFI can make optical damage and we have not observed the temporal spikes with InGaAs detector either. We still speculate that the OFI problem is one type of PL, dissimilar to an amplified spontaneous emission (ASE), with two basic phenomena: the backward spectrum is sharp and the gain is clamped around 1987 nm.…”
Section: Introductionmentioning
confidence: 64%
“…We name this problem optical feedback inhibition (OFI), and it may be similar to parasitic lasing (PL) also resulting from back reflection. Although parasitic lasing mostly occurs in high power or Q-switched high gain laser system, like slab laser, thin-disk laser or fiber amplifier, [13][14][15][16][17][18] and can make optical damage with spectrally bright and small spatial divergent beam, to date, no direct evidence has indicated that OFI can make optical damage and we have not observed the temporal spikes with InGaAs detector either. We still speculate that the OFI problem is one type of PL, dissimilar to an amplified spontaneous emission (ASE), with two basic phenomena: the backward spectrum is sharp and the gain is clamped around 1987 nm.…”
Section: Introductionmentioning
confidence: 64%
“…The output power is measured by an optical power meter (OPM). The pigtail fiber of the amplifier is a kind of all-solid photonic bandgap fiber for Yb band parasitic lasing suppression in Er/Yb co-doped fiber amplifier with a mode field diameter (MFD) of 10.9 µm at the wavelength of 1550 nm [33].…”
Section: Experimental Setup and Fiber Characteristicsmentioning
confidence: 99%
“…Instead of passively filtering the Yb-ASE either with specially designed long-period fiber gratings [4] or band-gap photonic crystal fibers [5,6], the strong Yb-ASE can be actively reused to improve the efficiency of an EYDFA [7][8][9][10]. In our previous works [7][8][9], we revealed through numerical investigation that in a high-power pumped EYDFA the counter-pump-propagating Yb-ASE is dominant.…”
Section: Introductionmentioning
confidence: 99%